THEORETICAL ANALYSIS OF PSYCHOLOGICAL CONDITIONS OF STUDENT EMPLOYMENT (Psychology Travelogs, 2021)
The article presents a theoretical analysis of psychological conditions of student employment. The concept of "employment" is analyzed, which means a system of measures aimed at ensuring employment, the positions of domestic and foreign scientists on the peculiarities of this process among different segments of the population in general and students in particular. The factors influencing the psychological state of the individual at the stage of job search and in the first stages after the beginning of employment are described. In order to more accurately and clearly analyze the peculiarities of youth employment, the formation of the labor market is analyzed, highlighting five key indicators that are key in this process. The study identified the main difficulties faced by student youth who are choosing a job or are already getting a job. At the same time, the regularities of the influence of personal self-esteem on the choice of workplace and salary, as well as the main problems that a student has to face at the initial stage of professionalization are studied. After analyzing the data, we have identified the main recommendations for students at the employment stage, which will promote a more comfortable entry into the work environment, increase the likelihood of a successful career, reduce the risk of frustration in the chosen field, stress and occupational deformity.
Keywords: employment; students; adolescence; psychological conditions; work stress; adaptation